Stopping plagiarism through enculturation: A practice-based approach - McDonald, Shirley; Adl, Ramine (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2019)
For the past decade or more, instructors in all disciplines and at all levels of education have worried about increased student misconduct and plagiarism. The rise in plagiarism is due, partly, to an evolving ethos among communities of users and providers who share open source media and, partly, to misleading models, such as Internet sources that offer information without crediting authors ((Buchanan & McKay, 2018). There has also been a rise in inadvertent plagiarism as international students arrive at Western universities and face the challenges of developing skills in a new language and of learning how to reference source materials (Howard, 2005; Lei & Hu, 2015; Li & Casanave, 2012; Pecorari, 2003). This paper explores the efficacy of the Academic Literacies Training in English (ALTE) method which the authors designed to help students develop skills in quoting and citing sources while fostering enculturation, an anthropological term, meaning welcoming students to become members of the community and embrace academic values (Wang 2008, p. 751). The value the authors seek to promote is that of intellectual property. Familiarizing students with the academic conventions of quoting and citing sources is essential to make them cognizant of the ethical and logical reasons for crediting scholars for their work (Jamieson, 2008; Maddox, 2008). The ALTE method integrates referencing, vocabulary, and grammar into writing instruction, using low-stakes exercises and formal assignments that serve as learning tools (Gibbs, 2010). In this paper, we discuss how the ALTE method, a systematic, practice-based approach in writing and referencing instruction, is an effective means of minimizing inadvertent plagiarism among lower-level university students.